ANALYSIS OF TREATMENT COMPLIANCE WITH TUBERCULOSIS (TB) PATIENTS IN TB MANAGEMENT PROGRAM IN JOHAN PAHLAWAN PUSKESMAS, ACEH BARAT REGENCY - Desi Nafitri SA; Safrizal Safrizal (RADJA PUBLIKA, 2022)
Tuberculosis is a chronic infectious disease caused by the bacterium Mycobacterium tuberculosis. Johan Pahlawan Puskesmas is the Puskesmas with the most TB cases compared to other Puskesmas based on the results of TB data reports from the West Aceh Health Office. There were 35 patients being treated based on 314 suspected cases reported from the Johan Pahlawan Health Center. The type of research used in this research is descriptive qualitative . In this study, the selection of informants was carried out using a purposive sampling method with a total of 5 informants. The data collection method in this research is by conducting in- depth interviews . The results of the study were determined based on several categories which were summarized from the results of in-depth interviews, some of these categories were formed into four themes, namely duration of TB treatment, knowledge about TB, presence of drug-taking supervisors and barriers to treatment. Researchers suggest to the health service unit to form a team of extension workers in providing education to the public, to health workers to be more proactive in monitoring the role of the Drug Swallowing Supervisor and patient regularity, and making agreements with patients to complete treatment.